Conditions of Compliance: Evaluating the Effectiveness of the UN Security Council - Jung, Yoonsun (Technium Social Sciences Journal, 2025)
This paper examines the effectiveness of United Nations Security Council (UNSC) sanctions in compelling target state compliance, focusing on three core hypotheses concerning state power, legal ambiguity, and strategic alliances with permanent council members. Through a mixed-methods approach combining legal analysis of the UN Charter’s Articles 25, 27, and 41 with detailed case studies of Libya, North Korea, and Iraq, the study identifies critical factors underlying compliance and non-compliance. The analysis reveals that vague legal mandates and weak enforcement mechanisms substantially undermine sanction effectiveness, enabling powerful states and their allies to evade consequences. Russia’s veto power emerges as a significant structural barrier, notably in the DPRK case, where it shields non-compliant behavior. Conversely, Libya’s eventual compliance illustrates the impact of legally binding, clear sanctions coupled with diplomatic isolation. The findings highlight the need for institutional reform, including conditional restrictions on veto use and an independent compliance mechanism, to strengthen the legitimacy and operational capacity of UNSC sanctions. This study contributes to understanding the interplay between international law, great power politics, and global governance challenges in sanctions enforcement.